2006
DOI: 10.1577/m06-035.1
|View full text |Cite
|
Sign up to set email alerts
|

Linking Angling Catch Rates and Fish Learning under Catch‐and‐Release Regulations

Abstract: Many recreational fisheries are subject to varying degrees of catch‐and‐release fishing through regulations and conservation‐minded anglers. Clearly, releasing a proportion of the catch improves conservation of the fishery, yet it is not clear how the released catch contributes to angling quality. If fish change their behavior to lower their individual catchability after they have been caught, then angler catch rates may not be proportional to fish density. Therefore, even catch‐and‐release fisheries could exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
122
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 19 publications
8
122
4
Order By: Relevance
“…Our results, although obtained from a single type of fishing gear, also should apply to fishing gear other than gillnets. For instance, trout in small lakes appear to be composed of highly vulnerable individuals that are rapidly caught by angling and individuals that more difficult to catch (22). Indeed, a recent study shows that vulnerability of fish to angling is a heritable trait in fish and is related to metabolic rate and some parental behaviors (23).…”
Section: Discussionmentioning
confidence: 99%
“…Our results, although obtained from a single type of fishing gear, also should apply to fishing gear other than gillnets. For instance, trout in small lakes appear to be composed of highly vulnerable individuals that are rapidly caught by angling and individuals that more difficult to catch (22). Indeed, a recent study shows that vulnerability of fish to angling is a heritable trait in fish and is related to metabolic rate and some parental behaviors (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, while evidence that fishing alters fish behaviour, and potentially fishing success, has been reported from freshwater recreational fisheries (Cox & Walters 2002, Askey et al 2006) and commercial trawls (Pyanov & Zhuykov 1993), knowledge of the influence of behavioural changes on catchability of coral reef fishes is lacking, despite indications that fishing can influence fish detectability (Kulbicki 1998). Using the metric flight initiation distance (FID), which estimates how close an animal can be approached before it flees (also referred to as flight or approach distance) (Ydenberg & Dill 1986), it has been established that fishes on near-shore, shallow reefs open to fishing consistently flee from an observer at a greater distance than fishes in notake marine reserves (NTRs) (Cole 1994, Gotanda et al 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson (1975) speculated that the evolution of the Florida bass in shallow-water habitats made it less vulnerable, while Johnson and Graham (1978) believed the Florida bass was more excitable. Several authors suggested that the differences observed in catchability were based on differences in wariness and learning ability (e.g., Beukema 1970;Rieger et al 1978;Askey et al 2006). In fact, Garrett (2002) used the differential vulnerability of the two species to select individuals from a mixed population of bass, and he went on to show that the vulnerability differences remained after breeding to produce a new generation of each.…”
mentioning
confidence: 99%